Transforming Philippine Agri-Food Systems with Digital Technology: Extent, Prospects, and Inclusiveness - Roehlano M. Briones; Ivory Myka R. Galang; Jokkaz S. Latigar (Philippine Institute for Development Studies (PIDS), 2023)
This study presents a rapid assessment of digital technology's adoption in Philippine agriculture and its implications for smallholder farmers. Modernization of agriculture, a perennial goal in agricultural policy, is increasingly linked with digital technologies, as outlined in the Philippine Development Plan (PDP) and underscored by Industry 4.0's transformative impacts on markets, trade, and manufacturing. Digital agriculture offers significant potential benefits, including enhanced productivity, market access, and sustainability. However, it also presents the risk of exacerbating the "digital divide," potentially leaving vulnerable rural populations further behind. The assessment explores the current application of digital technologies in agricultural value chains, the prospects for further adoption, and whether these technologies are benefiting the most vulnerable farmers and fisherfolk. Findings reveal that, while certain digital agriculture components like advisory apps and online retail networks are widespread, others remain in early development or at prototype stages. Government priorities and stakeholder interest (farmers, fisherfolk, agribusiness companies) suggest promising prospects for the expansion of digital agriculture tools, including decision support systems and online marketplaces. The study also identifies strategies to bridge the digital divide, such as community organizing, development of rental markets, and investments in rural connectivity. Key policy recommendations include harmonizing government data and advisory services, creating a single government portal for digital agriculture, integrating digital solutions into farm management, expanding decision support for diversification and climate resiliency, and establishing a centralized e-commerce platform. Emphasizing the importance of governmentled initiatives, the study advocates for exploring public-private partnerships to enhance the commercialization and accessibility of digital agricultural technologies.
Keywords: 330; digital agriculture; agri 4.0; precision agriculture; smart farming; e-commerce; fintech; digital divide